The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/2325967114529920
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of Glenoid Defects in Traumatic Anterior Shoulder Instability

Abstract: Background:Large glenoid rim defects in patients with traumatic anterior shoulder instability are often regarded as a contraindication for arthroscopic Bankart repair, with a defect of 20% to 27% considered as the critical size. While recurrence of dislocations, male sex, and collision sports were reported to be the significant factors influencing large glenoid defects, the influences of subluxations and more detailed types of sports were not investigated.Purpose:To investigate the influence of the number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 20 publications
3
44
0
Order By: Relevance
“…The correlation between the number of dislocation and the glenoid width defect was found to be significant ( p = 0.017). This result of the present study is similar to various other studies 15, 18, 20. The correlation between the number of dislocation and Hill-Sachs defect was also found to be significant ( p = 0.030).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The correlation between the number of dislocation and the glenoid width defect was found to be significant ( p = 0.017). This result of the present study is similar to various other studies 15, 18, 20. The correlation between the number of dislocation and Hill-Sachs defect was also found to be significant ( p = 0.030).…”
Section: Discussionsupporting
confidence: 92%
“…This result of the present study is similar to various other studies. 15 , 18 , 20 The correlation between the number of dislocation and Hill-Sachs defect was also found to be significant ( p = 0.030). While the other study has found that Hill-Sachs defect has significant correlations with initial trauma and relocation.…”
Section: Discussionmentioning
confidence: 80%
“…To quantify the glenoid defect, the inferior portion of the glenoid rim was approximated to a true circle on en face 3D-CT scans that had been reconstructed with elimination of the humeral head. 10 13 The extent of the glenoid defect was calculated as a percentage of the glenoid rim length by the equation B / A × 100%, where A is the diameter of the fitted circle and B is the width of the defect ( Figure 1A ). A Hill-Sachs lesion was diagnosed if an abnormal groove was detected on the posterolateral aspect of the head of the humerus.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that glenoid defects were seen in 20% of shoulders with primary instability and 66.2% of shoulders with recurrent instability. 11 Thus, glenoid rim fractures are not rare in unstable shoulders, and it has recently come to be considered that assessment of glenoid bone defects is required when planning surgery for traumatic anterior shoulder instability. However, CT has not been established as an essential tool for evaluating patients with postoperative recurrence of instability and repeated scanning should be avoided because of radiation exposure, so plain radiographic or magnetic resonance imaging is often performed instead after instability recurs.…”
Section: See Related Article On Page 2501mentioning
confidence: 99%